The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/antibiotics10020116
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Interferes with Streptococci Spatial Distribution and with Protein Expression of Species within a Polymicrobial Oral Biofilm

Abstract: We asked whether transient Staphylococcus aureus in the oral environment synergistically interacts with orally associated bacterial species such as Actinomyces oris, Candida albicans, Fusobacterium nucleatum, Streptococcus oralis, Streptococcus mutans, and Veillonella dispar (six-species control biofilm 6S). For this purpose, four modified biofilms with seven species that contain either the wild type strain of the S. aureus genotype (USA300-MRSA WT), its isogenic mutant with MSCRAMM deficiency (USA300-MRSA ΔMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 88 publications
0
7
0
1
Order By: Relevance
“…According to the biofilm matrix, the mechanisms of biofilm formation can be classified as either PIA-independent or PIA-dependent ( 32 ). Previous studies found that the biofilm formation of MSSA was PIA-dependent, and the MRSA was PIA-independent ( 33 , 34 ). In contrast, all strains whether MSSA or MRSA synthesize large amounts of PIA in our study.…”
Section: Discussionmentioning
confidence: 94%
“…According to the biofilm matrix, the mechanisms of biofilm formation can be classified as either PIA-independent or PIA-dependent ( 32 ). Previous studies found that the biofilm formation of MSSA was PIA-dependent, and the MRSA was PIA-independent ( 33 , 34 ). In contrast, all strains whether MSSA or MRSA synthesize large amounts of PIA in our study.…”
Section: Discussionmentioning
confidence: 94%
“…These species are main reservoirs of resistance genes, participating actively in the horizontal transmission of these genes to more virulent pathogens 6 , 53 , potentially including periodontal pathogens 57 . In addition, colonization of the dental biofilm by staphylococci may influence the virulence and structure of this complex oral community, triggering the change from a eubiotic biofilm to a dysbiotic one 32 34 , 58 . Using in vitro biofilm models, Lima et al 33 showed the ability of S. aureus to integrate and grow into a human-derived multispecies oral microbial community, affecting its composition.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between C. albicans and Staphylococcus spp. are apparently synergistic or mutualistic, and they are increasingly reported [ 43 ]. The findings suggest that fungal cells can modulate the action of antibiotics and that bacteria can affect antifungal activity in mixed fungal–bacterial biofilms [ 44 ].…”
Section: Discussionmentioning
confidence: 99%